PENGARUH SISTEM PENGENDALIAN INTERN DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH - Mokoginta, Novtania; Lambey, Linda; Pontoh, Winston (Universitas Sam Ratulangi, 2017)
Application of Internal Control System and Regional Financial Accounting System in management of local government financial statements is a very important thing. This financial statements of local governments must meet the following characteristics : relevant, reliable, comparable, and understandable. The purpose this study to examine the influence of the Internal Control System,Regional Financial Accounting System on the quality of goverment financial statements. The population in this study are all working in BPKAD Bolaang Mongondow Utara. The sample in this study is the staff / employees of the financial part of the respondents were 30 respondents. The samples were selected by using a purposive samplingmethod. Data was collected by distributing questionnaires to the respondents directly concerned. Technical analysis of the data used is multiple regression with SPSS 22. The result showed that : the Internal Control System has a significant effect on the quality of government financial statements and the Regional Financial Accounting System has a positive significant effect on the quality of goverment financial statements.Keywords : Internal Control system, Regional finsncisl accaounting system, quality of goverment financial statements.